1991
DOI: 10.1021/ac00020a021
|View full text |Cite
|
Sign up to set email alerts
|

Determination of site-specific carbon isotope ratios at natural abundance by carbon-13 nuclear magnetic resonance spectroscopy

Abstract: Site-specific natural isotope fractionation of hydrogen studied by deuterium NMR (SNIF-NMR) spectroscopy is a powerful source of information on hydrogen pathways occurring in biosyntheses in natural conditions. The potential of the carbon counterpart of this method has been investigated and compared. Three typical molecular species, ethanol, acetic acid, and vanillin, have been considered. Taking into account the requirements of quantitative 13C NMR, appropriate experimental procedures have been defined and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 24 publications
3
47
0
Order By: Relevance
“…As a result, the development of the technique took longer, starting from the first work (Caer et al, 1991) to the recent attainment of suitable acquisition conditions (Caytan et al, 2007a). A relative method of 13 C NMR was previously proposed as a way to calculate isotope effects in which the NMR signal intensity of the site-active carbon is related to the intensity of the signal of a 'neutral' carbon (far away from the active site), making the assumption that the latter is not modified during the chemical reaction (Singleton and Thomas, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the development of the technique took longer, starting from the first work (Caer et al, 1991) to the recent attainment of suitable acquisition conditions (Caytan et al, 2007a). A relative method of 13 C NMR was previously proposed as a way to calculate isotope effects in which the NMR signal intensity of the site-active carbon is related to the intensity of the signal of a 'neutral' carbon (far away from the active site), making the assumption that the latter is not modified during the chemical reaction (Singleton and Thomas, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…As a non-invasive method, NMR has played an important role in wine analysis, [1][2][3][4][13][14][15][16] especially in classification and characterization of the geographic origin and age of wine. [12][13][14][15][16][17][18][19][20][21][22][23][24][25] The method is widely used for analysis of metabolites in complex biological samples.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21][22][23][24][25] The method is widely used for analysis of metabolites in complex biological samples. [26][27][28] Since NMR spectroscopy needs nearly no sample pretreatment, the inherent chemical or biological properties of the sample are well kept and the error resulting from pretreatment may be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Currently 1 H and 13 C NMR spectroscopies are used for the detection of enrichment of musts by addition of sugars and for the identification of geographical origin [1,2]. It has been shown that 13 C NMR can successfully be used for detection of sugars, sugar alcohols and acids [3] and that 13 C resonances of amino acids can be used as fingerprints for the monitoring of European wines [4].…”
Section: Introductionmentioning
confidence: 99%